Self-monitored adaptive cache warm-up for microprocessor simulation - Luo, Y.; John, L. K.; Eeckhout, L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2004: Anais do XVI Symposium on Computer Architecture and High Performance Computing, 2004)
Simulation is the most important tool for computer architects to evaluate the performance of new computer designs. However, detailed simulation is extremely time consuming. Sampling is one of the techniques that effectively reduce simulation time. In order to achieve accurate sampling results, microarchitectural structure must be adequately warmed up before each measurement. In this paper, a new technique for warming up microprocessor caches is proposed. The simulator monitors the warm-up process of the caches and decides when the caches are warmed up based on simple heuristics. In our experiments the self-monitored adaptive (SMA) warm-up technique on average exhibits only 0.2% warm-up error in CPI. SMA achieves smaller warm-up error with only 1/2-1/3 of the warm-up length of previous methods. In addition, it is adaptive to the cache configuration simulated. For simulating small caches, the SMA technique can reduce the warm-up overhead by an order of magnitude compared to previous techniques. Finally, SMA gives the user some indicator of warm-up error at the end of the cycle-accurate simulation that helps the user to gauge the accuracy of the warm-up.